Visualising the Mycobacterial Mutasome - Reiche, Michael Anton (Department of Pathology, 2018)
An SOS-inducible DNA repair system has been linked to transient hyper-mutation and the development of drug resistance in Mycobacterium tuberculosis. Previous work has established that this “mycobacterial mutasome” comprises the specialist DNA polymerase, DnaE2, and accessory factors of unknown function, ImuA′ and ImuB. However, the molecular interactions and sub-cellular recruitment dynamics enabling mutasome function remain poorly understood. Here, a panel of fluorescent strains of M. smegmatis was developed to investigate expression and subcellular localization of ImuA′ and ImuB in live mycobacteria exposed to genotoxic agents. Using fluorescence microscopy, it was observed that, during prolonged genotoxic stress, single M. smegmatis cells exhibited an elongated cell phenotype and apparent aneuploidy – potentially providing an environment for recombination between differentially mutated chromosomes. Furthermore, ImuB was seen to associate with the dnaNencoded β clamp in discrete foci during mutagenic DNA repair. In contrast, ImuA′ did not exhibit similar localization and instead appeared to diffuse throughout the bacillus. A mutant ImuB protein deficient in the β clamp-binding motif failed to colocalize with the β clamp, reinforcing the inferred essentiality of the ImuB-β clamp protein-protein interaction for mutasome recruitment and induced mutagenesis. Additionally, exposure of M. smegmatis to griselimycin, a novel β clamp-targeting natural product antibiotic, prevented ImuB-β clamp co-localization during SOS induced mutagenesis, an observation confirmed by superresolution, threedimensional interferometric photo-activated light microscopy. These results establish the capacity of griselimycin to inhibit DNA replication as well as prevent DNA damage-induced mutagenesis by disrupting mutasome assembly and activity. Notably, this differentiates griselimycin from other inhibitors of DNA metabolic function which carry the often-unavoidable liability of accelerating drug-resistance by inducing mutagenic DNA repair. In turn, it suggests the potential application of griselimycin as an anti-evolution agent in novel therapeutic regimens designed to protect existing tuberculosis drugs.